Examining the Influence of Human Resource Practices on Knowledge Management Practices: A Case Study of Sarang Oci Restaurant in Jakarta - Wibisono, Nicholaus Alphadimas; Caroline, Angela (The International Journal of Business Review (The Jobs Review), 2024)
Previous studies have shown that human resource management influences knowledge management. By having knowledge management, companies can create new knowledge, store knowledge in a more orderly manner, increase the possibility of sharing knowledge, and increase the application of knowledge to workers. So from this perspective, companies are advised to manage human resources and ensure it’s good application. The purpose of this study was to examine the effect of Human Resource Practice on Knowledge Management Practice at Sarang Oci Restaurant. Sarang Oci, which is the object of this research, is a Manadonese restaurant located in Jakarta. The research type is explanatory. Data collection was carried out using questionnaires. The questionnaire obtained 133 respondents from a population of 190 people. After that the data is processed through seven tests, namely Validity Test, Reliability Test, Normality Test, Heteroscedasticity Test (Glejser), Simple Linear Regression Effect Test, and Coefficient of Determination Test. To measure the effect of Human Resource Practice on Knowledge Management Practice. From this research it can be seen that at Sarang Oci Restaurant Knowledge Management Practice is influenced by 14.1% by Human Resource Practice.